STUDI FILOSOFIS TERHADAP TARI TANGGAI DI KOTA PALEMBANG - Naomi Diah Budi Setyaningrum (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstactThis is articel about it raised The Philosophy values from Tari Tanggai dance in social community of Palembang people and pour it’s values in the Philosophy of Phenomenology Art. To uncover these values so that’s why the researcher uses the qualitative methods. The data was collected by using the references, field observations and interviews. In solving this problem, the researcher used the phenomenology approach. The result from the research shows that Tari Tanggai as a welcoming dance for Palembang people as an attribute to give honour to the guests using Tanggai. Tanggai dance in society contains the Philosophy values in it’s moving like; in the movement of Siguntang Mahameru, Borobudur,, Stupa, Mudra, Sembah and Tolak Arus. While, Tanggai dance in society life has function for religious, for performance art, for education, and for the performance of tourism package Keywords: Tanggai dance, Philosophy values and functions